2014
DOI: 10.1088/1742-5468/2014/03/p03005
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of Turing pattern formation in a positive feedback system with cross diffusion

Abstract: In this paper, we analyze a reaction–diffusion (R–D) system with a double negative feedback loop and find cases where self diffusion alone cannot lead to Turing pattern formation but cross diffusion can. Specifically, we first derive a set of sufficient conditions for Turing instability by performing linear stability analysis, then plot two bifurcation diagrams that specifically identify Turing regions in the parameter phase plane, and finally numerically demonstrate representative Turing patterns according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Usually, dynamical processes are modeled by reaction-diffusion (RD) systems, which have been widely employed over decades to characterize the evolution in dynamical systems, in which local elements diffuse and interact with a certain way. Many efforts [2][3][4][5][6][7][8][9][10][11] have been carried out to analyze heterogeneous RD processes, since Turing [12] showed that the formation of a periodic spatial pattern can be inspired by perturbation around the equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, dynamical processes are modeled by reaction-diffusion (RD) systems, which have been widely employed over decades to characterize the evolution in dynamical systems, in which local elements diffuse and interact with a certain way. Many efforts [2][3][4][5][6][7][8][9][10][11] have been carried out to analyze heterogeneous RD processes, since Turing [12] showed that the formation of a periodic spatial pattern can be inspired by perturbation around the equilibrium.…”
Section: Introductionmentioning
confidence: 99%